Location selection of bicycle sharing delivery points based on rebalancing supply and demand - Hanqiang Qian; Yanyan Chen; Shuyan Zheng; Yue Shi (Journal of Highway and Transportation Research and Development, 2025)
As a green travel option, the bicycle sharing system has seen rapid development in recent years. Where to put the repaired bicycles and new bicycles becomes a real problem. It is necessary to help the bicycle sharing system rebalance the supply and demand. Moreover, it is also important to ensure the quickly use for new bicycles. Based on the realistic demand for bicycle sharing, this paper designs a strategy to select the location of bicycle sharing delivery points. The strategy considers the current supply and demand as well as travel intensity. Based on mobile signaling data and bicycle sharing data, the potential demand for bicycle sharing use is identified firstly. Next, the distribution of bicycle sharing is recognized. Then the supply and demand of bicycle sharing are analyzed. Finally, travel hotspots are identified and the location of bicycle sharing delivery points is extracted. Taking Beijing as a case study, more effective delivery points within the fifth ring road were identified. The application of the method can help improve the operational efficiency of the bicycle sharing system and promote the sustainable development of urban transportation.